Case Report: Parsonage-Turner syndrome due to SEPTIN9 mutation: report of an Italian family with childhood onset and review of the literature - Bosisio, Luca; Cataldi, Matteo; Grandis, Marina; Tappino, Barbara; Traverso, Monica; Germano, Francesco; Nobili, Lino; Fiorillo, Chiara (Frontiers in Pediatrics, 2025)
AimParsonage-Turner syndrome, also known as neuralgic amyotrophy affects the brachial plexus and includes idiopathic (INA) and rare hereditary forms (HNA). Mutations in the SEPTIN9 gene, which encodes a cytoskeletal GTPase, have been implicated in HNA. While Parsonage-Turner syndrome is typically adult-onset, with stress often acting as a trigger, the presentation in children is less acknowledged.MethodsWe report a case of 9-year-old girl with brachial plexus neuritis who carries a SEPTIN9 missense mutation inherited from her father. We conducted a literature review to explore early-onset cases and gain insight into the disease's progression over time.ResultsPatient presented with episodic intense pain and severe weakness in her right upper limb since age 5 years. Central nervous system involvement and inflammatory polyneuropathy were excluded. Neurological assessment showed weakness and muscle atrophy in the right shoulder girdle. Dysmorphic features, such as long nasal bridge, hypertelorism, and epicanthal folds, were also noted. Her father reported a similar episode in the past without investigations. SEPTIN9 gene sequencing revealed the missense mutation (c.262C>T; p.Arg88Trp) in both individuals. The review of 109 patients with hereditary neuropathy linked to SEPTIN9 mutations revealed a mean age of onset at 13 years, though the average time from symptom onset to diagnosis was 22 years. The syndrome typically follows a relapsing-remitting course, but monophasic and progressive forms are also described.ConclusionClinicians should consider HNA in children with asymmetric upper limb weakness and dysmorphic features, especially with a family history of upper limb neuralgia. Early diagnosis can improve long-term outcomes and avoid unnecessary tests.